Ruthenium-cobalt bimetallic catalyst stable in water-phase reduction of demethylation modified sodium lignin sulfonate
The sodium lignin sulfonate was demethylated by the sodium sulfite method to prepare the aqueous phase dispersed ruthenium cobalt bimetallic catalyst Ru-Co@DMSLSaq, which solved the problem that lignin derivatives in the prior art are difficult to reduce and stabilize non-precious metals in the aqueous phase, and achieved efficient catalytic performance and cost reduction.
Patent Information
- Application Number
- CN202411971514.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to effectively reduce and stabilize non-precious metals, such as ruthenium cobalt bimetals, in the aqueous phase by lignin derivatives, limiting their widespread use in catalyst applications.
Sodium lignin sulfonate was demethylated by sodium sulfite method to improve its hydroxyl content and in-situ reduction ability of metals, and a water-dispersed ruthenium cobalt bimetallic catalyst Ru-Co@DMSLSaq was prepared.
The stable reduction of ruthenium-cobalt bimetal in the aqueous phase was achieved, which reduced the catalyst cost, and showed excellent catalytic performance in the hydrogenation reaction of diphenylmethane and o-hydroxydiphenylmethane, which could efficiently prepare dicyclohexylmethane and all-hydrofluorene.
Smart Images

Figure CN119771441A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation and application of a demethylated modified sodium lignin sulfonate aqueous phase reduction-stabilized ruthenium-cobalt bimetallic catalyst, specifically, the sodium lignin sulfonate demethylated by a sodium sulfite method is used to in-situ reduce and stabilize ruthenium acetate and cobalt acetate in an aqueous solution to prepare a water-phase dispersed bimetallic catalyst, and the application of the bimetallic catalyst in the hydrogenation reaction of diphenylmethane and o-hydroxydiphenylmethane, belonging to the technical field of preparation and application of novel environmentally friendly catalysts. Background Art
[0002] Lignin is the second most abundant biomacromolecule resource on Earth, but its processing and utilization with high added value are far from enough. It has been found that the aromatic ring skeleton structure of lignin contains a large number of beneficial chemical groups, which can be broken down into small fragment compounds including aromatic hydrocarbons and various phenols, and has the potential to be modified or functionalized to prepare efficient catalysts.
[0003] In recent years, it has been found that water-soluble derivatives of lignin can act as both reducing agents and stabilizers in water to prepare water-dispersed precious metal nanoparticles. These methods for preparing water-dispersed metal nanoparticles constructed using lignin resources are clean, gentle, and have low operating costs. They eliminate the use of hazardous chemicals and petroleum-based chemicals and can be used as chemical probes for detecting heavy metals, signal amplifiers at the center of SERS technology, or as catalysts in certain redox reactions [ColloidsSurf B Biointerfaces.2013,105:335–341; Int J Biol Macromol.2016,82:856–862; Mater Lett.2015,159:451–454; ACS Omega.2020,5(15):8902–8911; Green Chem.2012,14(4):1073; Inorganica Chim Acta.2013,399:12–18; Ind Crops Prod.2023,192:116055]. However, since these lignin derivatives have only been found to be able to effectively reduce and stabilize precious metals in aqueous phase and have limited ability to act on non-precious metals, this limits their application as environmentally friendly catalysts.
[0004] Other studies have found that chemical modification methods such as phenolization and amination can improve the reactivity of lignin macromolecular structures, thereby enhancing their ability to interact with metal ions. For example, Inoue et al. prepared phenolic modified lignin gel materials for treating Pb(II) in wastewater [Materials. 2017, 10(8): 857]. Zhang et al. introduced pyrogallol into the alkaline lignin structure to increase the phenolic hydroxyl content, which is beneficial to the removal of Cr(VI) [J. Water Process. Eng. 2022, 50: 103334]. Ding et al. introduced amino-rich polymers into lignin phenolic hydroxyl substrates, significantly improving the capture ability of Cr(VI) [Int J Biol Macromol. 2023, 256(P2): 128358–128358]. In addition, in lignin macromolecules, the ortho positions of the phenolic hydroxyl groups in the guaiacyl structural unit and the syringyl structural unit are both methoxy groups, which have a steric hindrance to the phenolic hydroxyl reaction active sites to a certain extent. If these methyl groups can be removed by biological, thermal catalytic or chemical means, thereby increasing the phenolic hydroxyl content in the lignin structure, it will also play a role in improving its reactivity. Sawamura et al. found that the iodocyclohexane demethylation method can more effectively increase the phenolic hydroxyl content than HI or thiol [Acs Sustain Chem Eng. 2017, 5 (6): 5424-5431]. Kobayashi et al. used the iodocyclohexane method to demethylate and generate G / S or S-type lignin polymer models [J Wood Sci. 2022, 68 (1): 51]. Zhao et al. developed a strategy for demethylating enzymatic lignin in a halogen-free proton ionic liquid, with a demethylation rate of up to 73% under mild conditions [Chem. Eng. J. 2022, 443: 136486]. Du et al. used AlCl3 as a modification agent to promote demethylation to increase the phenolic hydroxyl content of lignin, which can effectively treat organic dyes in wastewater [J. Mol. Liq. 2023, 382]. Qiu et al. used Na2SO3 to demethylate sodium lignin sulfonate and prepared light-colored sodium lignin sulfonate microcapsules as broad-spectrum UV blockers and antioxidants for advanced skin care products [Acs Sustain Chem Eng. 2022, 10: 9381-9388]. Zhan used Na2SO3 to demethylate and hydrothermally degrade lignin to obtain highly reactive co-modified lignin, which enhanced the comprehensive performance of glue-free fiberboard [Ind Crops Prod. 2022, 177: 114452].Han used Na2SO3 to catalyze the demethylation of poplar lignin, pine lignin and rice husk lignin, and efficiently prepared lignin-based polyphenol compounds with high phenolic hydroxyl content, small molecular weight, strong antioxidant activity and low cytotoxicity [Sustainable Chem. Phar. 2023, 36: 101312].
[0005] In summary, Na2SO3 has an excellent demethylation effect on lignin, providing a clean lignin demethylation route. However, to date, there has been no literature report on the use of Na2SO3 demethylation and other modification methods to increase the phenolic hydroxyl content, improve the ability of sodium lignin sulfonate to reduce and stabilize metals, and prepare bimetallic catalysts containing non-precious metal components, and apply them to the hydrogenation of diphenylmethane and o-hydroxydiphenylmethane to efficiently prepare dicyclohexylmethane and perhydrofluorene, respectively. Summary of the invention
[0006] The purpose of the present invention is to use a sodium sulfite method to demethylate and modify sodium lignin sulfonate, a cheap and readily available industrial byproduct, so as to increase its hydroxyl content and its in-situ reduction ability to metals, thereby providing a water-phase reduction-stable ruthenium-cobalt bimetallic catalyst and a clean preparation method thereof. The present invention also provides an efficient application of the catalyst in the hydrogenation reaction of diphenylmethane and o-hydroxydiphenylmethane.
[0007] According to the present invention, the demethylated modified sodium lignin sulfonate aqueous phase reduction stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS is provided. aq The preparation method is as follows:
[0008] The vacuum-dried sodium lignin sulfonate was dissolved in a 1–10% aqueous sodium hydroxide solution at a ratio of 3 mL solution per gram of sodium lignin sulfonate, and anhydrous sodium sulfite was added at a ratio of 0.02–0.3 g per gram of sodium lignin sulfonate, stirred until fully dissolved, reacted at 60–100°C for 1.5 h, and then the mixture was placed in a dialysis bag and dialyzed to neutrality, dried and ground into powder to obtain demethylated modified sodium lignin sulfonate DMSLS. -3 Different amounts of ruthenium acetate and cobalt acetate were weighed, added to the measured ultrapure water and ultrasonicated until completely dissolved, and then added dropwise to the demethylated modified sodium lignin sulfonate aqueous solution, and ultrapure water was added until the concentration of demethylated sodium lignin sulfonate was 10 g / L. After stirring at 400 rpm and 60 ° C for 3 h, it was cooled to room temperature and diluted ten times with ultrapure water to obtain a stable black opaque aqueous ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS aq .
[0009] According to the present invention, the demethylated modified sodium lignin sulfonate aqueous phase reduction stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS is provided. aq The methods of use in the hydrogenation of diphenylmethane and o-hydroxydiphenylmethane are as follows:
[0010] According to the ratio of 6 mL aqueous catalyst per mmol of diphenylmethane, diphenylmethane and demethylated modified sodium lignin sulfonate were added to a stainless steel autoclave to reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in aqueous phase. aq After replacing the air in the kettle with hydrogen, the reaction was carried out for 4 hours under stirring at 400 rpm, a hydrogen pressure of 1.5 MPa and 80°C. After the reaction was completed, the aqueous phase catalyst was recovered by standing and separating the liquids, and the above steps were repeated to use it for the next cycle of catalytic reaction.
[0011] According to the ratio of 6 mL of aqueous catalyst per mmol of o-hydroxydiphenylmethane, o-hydroxydiphenylmethane and demethylated sodium lignin sulfonate were added to a stainless steel autoclave to reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS. aq After replacing the air in the kettle with hydrogen, the reaction was carried out for 4 hours under stirring at 400 rpm, a hydrogen pressure of 1.5 MPa and 90°C. After the reaction was completed, the liquid was allowed to stand and separated to recover the aqueous phase catalyst, and the above steps were repeated to use it for the next cycle of catalytic reaction.
[0012] The present invention provides a demethylated modified sodium lignin sulfonate aqueous phase reduction stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS aq Compared with the existing technology, it has the following characteristics:
[0013] (1) The sodium sulfite method was used to demethylate the modified sodium lignin sulfonate, and for the first time, the in-situ reduction and stabilization of the ruthenium-cobalt bimetallic in water phase was achieved, which greatly reduced the cost of the metal nanoparticle catalyst for lignin water phase stabilization.
[0014] (2) Aqueous ruthenium-cobalt bimetallic catalyst Ru-Co@DMSLS prepared under clean and mild conditions aq It has excellent catalytic ability in the hydrogenation reaction of diphenylmethane and o-hydroxydiphenylmethane, and can achieve high yield preparation of dicyclohexylmethane and perhydrofluorene products under mild aqueous phase reaction conditions. The catalyst can be recycled and has good cyclic stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Attached Figure 1 The sodium lignin sulfonate (SLS) and the sodium lignin sulfonate (DMSLS-1, DMSLS-3 and DMSLS-4) modified by demethylation in 1%, 5% and 10% sodium hydroxide solution in Example 1, Example 3 and Example 4 respectively are 1HNMR spectrum comparison. The peak at 4.7ppm in all sample spectra shown in the figure is the solvent peak of D2O, and the peak at 6.3-7.3ppm is the aromatic proton peak of the lignin molecule; the sharp peak group near 3.75ppm in the sodium lignin sulfonate spectrum is the methoxy proton peak; in the demethylated sample spectrum, the methoxy peak weakens, and the proton peaks of the ortho-diphenol and vicinal triphenol fragments in the lignin structure appear at 2.8ppm and 2.9ppm, and the active hydrogen peak of the phenolic hydroxyl group appears at 7.9ppm. The peak height of these two characteristic peaks is the strongest in the DMSLS-3 sample.
[0016] Attached Figure 2 The demethylated modified sodium lignin sulfonate aqueous phase reduction-stable ruthenium-cobalt bimetallic catalyst Ru-Co@DMSLS prepared in Example 3 aq -3 XPS total spectrum (a), Ru 3p fine spectrum (b) and Co 2p fine spectrum (c). Figure 2 (a) It can be seen that the sample contains two metal components, Ru and Co; Figure 2 (b) Display Ru 3+ Most of them are reduced, located at 484.21eV and 462.08eV Ru 0 The 3p characteristic peak accounts for about 90.81% of the Ru species; Figure 2 (c) Display Co 2+ The reduction degree is lower than that of Ru, and the Co at 781.98eV and 797.60eV 0 The 2p characteristic peak accounts for about 70.57% of the Co species. DETAILED DESCRIPTION
[0017] The following examples are used to further illustrate the present invention, but are not intended to limit the present invention.
[0018] [Example 1] Ru-Co@DMSLS aq -1 preparation and catalytic application
[0019] 5 g of vacuum-dried sodium lignin sulfonate was dissolved in 15 mL of 1 wt% NaOH aqueous solution, 1.0 g of anhydrous sodium sulfite was added and stirred evenly, the mixture was reacted at 90° C. for 1.5 h, dialyzed to neutrality in a dialysis bag, dried and ground into powder to obtain demethylated modified sodium lignin sulfonate DMSLS-1.
[0020] 60 mg of DMSLS-1 was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.06 mmol of ruthenium acetate and 0.04 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the DMSLS-1 aqueous solution. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a black opaque aqueous ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS aq -1.
[0021] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -1 and 1 mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5 MPa H2 was filled in, and the reaction was carried out at 80 °C for 4 h under stirring at 400 rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0022] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -1 and 1 mmol of o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen for 4-5 times, and then 1.5 MPa of H2 was filled in, and the reaction was carried out at 90 °C for 4 h under stirring at 400 rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0023] [Example 2] Ru-Co@DMSLS aq -2 preparation and catalytic application
[0024] 5 g of vacuum-dried sodium lignin sulfonate was dissolved in 15 mL of 2 wt% NaOH aqueous solution, 1.0 g of anhydrous sodium sulfite was added and stirred evenly, the mixture was reacted at 90° C. for 1.5 h, dialyzed to neutrality in a dialysis bag, dried and ground into powder to obtain demethylated modified sodium lignin sulfonate DMSLS-2.
[0025] 60 mg of DMSLS-2 was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.06 mmol of ruthenium acetate and 0.04 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the DMSLS-2 aqueous solution. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a black opaque aqueous ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS aq -2.
[0026] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -2 and 1 mmol of diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5 MPa of H2 was filled in, and the reaction was carried out at 80 °C for 4 h under stirring at 400 rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0027] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -2 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPa H2 was filled in, and the reaction was carried out at 90℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0028] [Example 3] Ru-Co@DMSLS aq -3 preparation and catalytic application
[0029] 5 g of vacuum-dried sodium lignin sulfonate was dissolved in 15 mL of 5 wt% NaOH aqueous solution, 1.0 g of anhydrous sodium sulfite was added and stirred evenly, the mixture was reacted at 90° C. for 1.5 h, dialyzed to neutrality in a dialysis bag, dried and ground into powder to obtain demethylated modified sodium lignin sulfonate DMSLS-3.
[0030] 60 mg of DMSLS-3 was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.06 mmol of ruthenium acetate and 0.04 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the DMSLS-3 aqueous solution. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a black opaque aqueous ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS aq -3.
[0031] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -3 and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPa H2 was filled in, and the reaction was carried out at 80℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0032] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase.aq -3 and 1 mmol of o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5 MPa of H2 was filled in, and the reaction was carried out at 90 °C for 4 h under stirring at 400 rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0033] [Example 4] Ru-Co@DMSLS aq -4 preparation and catalytic application
[0034] 5 g of vacuum-dried sodium lignin sulfonate was dissolved in 15 mL of 10 wt% NaOH aqueous solution, 1.0 g of anhydrous sodium sulfite was added and stirred evenly, the mixture was reacted at 90° C. for 1.5 h, dialyzed to neutrality in a dialysis bag, dried and ground into powder to obtain demethylated modified sodium lignin sulfonate DMSLS-4.
[0035] 60 mg of DMSLS-4 was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.06 mmol of ruthenium acetate and 0.04 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the DMSLS-4 aqueous solution. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a black opaque aqueous ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS aq -4.
[0036] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -4 and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPa H2 was filled in, and the reaction was carried out at 80℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0037] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -4 and 1 mmol of o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5 MPa of H2 was filled in, and the reaction was carried out at 90 °C for 4 h under stirring at 400 rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0038] [Example 5] Ru-Co@DMSLS aq -5 preparation and catalytic application
[0039] 5 g of vacuum-dried sodium lignin sulfonate was dissolved in 15 mL of 5 wt% NaOH aqueous solution, 1.0 g of anhydrous sodium sulfite was added and stirred evenly, the mixture was reacted at 60° C. for 1.5 h, dialyzed to neutrality in a dialysis bag, dried and ground into powder to obtain demethylated modified sodium lignin sulfonate DMSLS-5.
[0040] 60 mg of DMSLS-5 was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.06 mmol of ruthenium acetate and 0.04 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the DMSLS-5 aqueous solution. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a black opaque aqueous ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS aq -5.
[0041] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -5 and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPa H2 was filled in, and the reaction was carried out at 80℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0042] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -5 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPa H2 was filled in, and the reaction was carried out at 90℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0043] [Example 6] Ru-Co@DMSLS aq -6 preparation and catalytic application
[0044] 5 g of vacuum-dried sodium lignin sulfonate was dissolved in 15 mL of 5 wt% NaOH aqueous solution, 1.0 g of anhydrous sodium sulfite was added and stirred evenly, the mixture was reacted at 80° C. for 1.5 h, dialyzed to neutrality in a dialysis bag, dried and ground into powder to obtain demethylated modified sodium lignin sulfonate DMSLS-6.
[0045] 60 mg of DMSLS-6 was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.06 mmol of ruthenium acetate and 0.04 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the DMSLS-6 aqueous solution. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a black opaque aqueous ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS aq -6.
[0046] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -6 and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPa H2 was filled in, and the reaction was carried out at 80℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0047] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -6 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPa H2 was filled in, and the reaction was carried out at 90℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0048] [Example 7] Ru-Co@DMSLS aq -7 preparation and catalytic application
[0049] 5 g of vacuum-dried sodium lignin sulfonate was dissolved in 15 mL of 5 wt% NaOH aqueous solution, 1.0 g of anhydrous sodium sulfite was added and stirred evenly, the mixture was reacted at 100° C. for 1.5 h, dialyzed to neutrality in a dialysis bag, dried and ground into powder to obtain demethylated modified sodium lignin sulfonate DMSLS-7.
[0050] 60 mg of DMSLS-7 was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.06 mmol of ruthenium acetate and 0.04 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the DMSLS-7 aqueous solution. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a black opaque aqueous ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS aq -7.
[0051] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -7 and 1 mmol of diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5 MPa of H2 was filled in, and the reaction was carried out at 80 °C for 4 h under stirring at 400 rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0052] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -7 and 1 mmol of o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5 MPa of H2 was filled in, and the reaction was carried out at 90 °C for 4 h under stirring at 400 rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0053] [Example 8] Ru-Co@DMSLS aq -8 preparation and catalytic application
[0054] 5 g of vacuum-dried sodium lignin sulfonate was dissolved in 15 mL of 5 wt% NaOH aqueous solution, 0.1 g of anhydrous sodium sulfite was added and stirred evenly, the mixture was reacted at 90° C. for 1.5 h, dialyzed to neutrality in a dialysis bag, dried and ground into powder to obtain demethylated modified sodium lignin sulfonate DMSLS-8.
[0055] 60 mg of DMSLS-8 was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.06 mmol of ruthenium acetate and 0.04 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the DMSLS-8 aqueous solution. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a black opaque aqueous ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS aq -8.
[0056] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -8 and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPa H2 was filled in, and the reaction was carried out at 80℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0057] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase.aq -8 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPa H2 was filled in, and the reaction was carried out at 90℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0058] [Example 9] Ru-Co@DMSLS aq -9 preparation and catalytic application
[0059] 5 g of vacuum-dried sodium lignin sulfonate was dissolved in 15 mL of 5 wt% NaOH aqueous solution, 0.5 g of anhydrous sodium sulfite was added and stirred evenly, the mixture was reacted at 90° C. for 1.5 h, dialyzed to neutrality in a dialysis bag, dried and ground into powder to obtain demethylated modified sodium lignin sulfonate DMSLS-9.
[0060] 60 mg of DMSLS-9 was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.06 mmol of ruthenium acetate and 0.04 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the DMSLS-9 aqueous solution. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a black opaque aqueous ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS aq -9.
[0061] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -9 and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPa H2 was filled in, and the reaction was carried out at 80℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0062] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -9 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPa H2 was filled in, and the reaction was carried out at 90℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0063] [Example 10] Ru-Co@DMSLS aq Preparation and catalytic application of -10
[0064] 5 g of vacuum-dried sodium lignin sulfonate was dissolved in 15 mL of 5 wt% NaOH aqueous solution, 1.5 g of anhydrous sodium sulfite was added and stirred evenly, the mixture was reacted at 90° C. for 1.5 h, dialyzed to neutrality in a dialysis bag, dried and ground into powder to obtain demethylated modified sodium lignin sulfonate DMSLS-10.
[0065] 60 mg of DMSLS-10 was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.06 mmol of ruthenium acetate and 0.04 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the DMSLS-10 aqueous solution. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a black opaque aqueous ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS aq -10.
[0066] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -10 and 1 mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5 MPa H2 was filled in, and the reaction was carried out at 80 °C for 4 h under stirring at 400 rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0067] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -10 and 1 mmol of o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5 MPa of H2 was filled in, and the reaction was carried out at 90 °C for 4 h under stirring at 400 rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0068] [Example 11] Ru-Co@DMSLS aq -11 preparation and catalytic application
[0069] 5 g of vacuum-dried sodium lignin sulfonate was dissolved in 15 mL of 5 wt% NaOH aqueous solution, 1.0 g of anhydrous sodium sulfite was added and stirred evenly, the mixture was reacted at 90° C. for 1.5 h, dialyzed to neutrality in a dialysis bag, dried and ground into powder to obtain demethylated modified sodium lignin sulfonate DMSLS-3.
[0070] 60 mg of DMSLS-3 was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.05 mmol of ruthenium acetate and 0.05 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the DMSLS-3 aqueous solution. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a black opaque aqueous ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS aq -11.
[0071] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -11 and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPa H2 was filled in, and the reaction was carried out at 80℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0072] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -11 and 1 mmol of o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5 MPa of H2 was filled in, and the reaction was carried out at 90 °C for 4 h under stirring at 400 rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0073] [Example 12] Ru-Co@DMSLS aq Preparation and catalytic application of -12
[0074] 5 g of vacuum-dried sodium lignin sulfonate was dissolved in 15 mL of 5 wt% NaOH aqueous solution, 1.0 g of anhydrous sodium sulfite was added and stirred evenly, the mixture was reacted at 90° C. for 1.5 h, dialyzed to neutrality in a dialysis bag, dried and ground into powder to obtain demethylated modified sodium lignin sulfonate DMSLS-3.
[0075] 60 mg of DMSLS-3 was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.04 mmol of ruthenium acetate and 0.06 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the DMSLS-3 aqueous solution. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm. After cooling to room temperature, it was diluted ten times with ultrapure water to obtain a black opaque aqueous ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS aq -12.
[0076] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -12 and 1mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPa H2 was filled in, and the reaction was carried out at 80℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 1.
[0077] Take 6 mL of the above-prepared demethylated modified sodium lignin sulfonate and reduce the stable ruthenium cobalt bimetallic catalyst Ru-Co@DMSLS in water phase. aq -12 and 1 mmol of o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5 MPa of H2 was filled in, and the reaction was carried out at 90 °C for 4 h under stirring at 400 rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 2.
[0078] [Examples 13-16] Ru-Co@DMSLS aq -3 cycle performance
[0079] The mixed system after the catalytic reaction of diphenylmethane in Example 3 was allowed to stand for separation to remove the upper organic phase, and the recovered aqueous catalyst was added to a stainless steel autoclave, and then 1 mmol of diphenylmethane was added, and the air was replaced with hydrogen for 4-5 times, and then 1.5 MPa of H2 was filled, and the reaction was carried out at 80°C for 4 hours under stirring at 400 rpm. After the reaction was completed, the mixed reaction system was taken out and allowed to stand for separation, and the upper organic phase was taken for gas chromatography analysis, and the above operation was repeated for the recovered aqueous catalyst. The results of recycling for 4 times are shown in Table 3.
[0080] The mixed system after the catalytic reaction of o-hydroxydiphenylmethane in Example 3 was allowed to stand for separation to remove the upper organic phase, and the recovered aqueous catalyst was added to a stainless steel autoclave, and then 1 mmol of o-hydroxydiphenylmethane was added, and the air was replaced with hydrogen for 4-5 times, and then 1.5 MPa H2 was filled, and the reaction was carried out at 90°C for 4 hours under stirring at 400 rpm. After the reaction was completed, the mixed reaction system was taken out and allowed to stand for separation, and the upper organic phase was taken for gas chromatography analysis, and the above operation was repeated for the recovered aqueous catalyst. The results of recycling for 4 times are shown in Table 4.
[0081] Table 1 Hydrogenation of diphenylmethane catalyzed by demethylated sodium lignin sulfonate with aqueous phase reduction-stable ruthenium-cobalt bimetallic catalyst
[0082]
[0083] Table 2 Hydrodeoxygenation of o-hydroxydiphenylmethane catalyzed by demethylated sodium lignin sulfonate with aqueous reduction-stabilized ruthenium-cobalt bimetallic catalyst
[0084]
[0085] Table 3Ru-Co@DMSLS aq -3 Catalytic performance of diphenylmethane hydrogenation
[0086]
[0087] Table 4Ru-Co@DMSLS aq -3 catalyzes the hydrodeoxygenation of o-hydroxydiphenylmethane for recycling
[0088]
[0089] [Comparative Example 1] Ru-Co@SLS aq -1 preparation and catalytic performance
[0090] 60 mg of sodium lignin sulfonate was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.06 mmol of ruthenium acetate and 0.04 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the sodium lignin sulfonate aqueous solution. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm, cooled to room temperature, and diluted ten times with ultrapure water to obtain Ru-Co@SLS. aq -1.
[0091] Take 6 mL of the sodium lignin sulfonate prepared above and reduce the stabilized ruthenium-cobalt bimetallic catalyst Ru-Co@SLS in water phase. aq -1 and 1 mmol diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5 MPa H2 was filled in, and the reaction was carried out at 80 °C for 4 h under stirring at 400 rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 5.
[0092] Take 6 mL of the sodium lignin sulfonate prepared above and reduce the stabilized ruthenium-cobalt bimetallic catalyst Ru-Co@SLS in water phase. aq -1 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPaH2 was filled in, and the reaction was carried out at 90℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 6.
[0093] [Comparative Example 2] Ru-Co@SLS aq -2 preparation and catalytic performance
[0094] 60 mg of sodium lignin sulfonate was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.05 mmol of ruthenium acetate and 0.05 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the sodium lignin sulfonate aqueous solution. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm, cooled to room temperature, and diluted ten times with ultrapure water to obtain Ru-Co@SLS. aq -2.
[0095] Take 6 mL of the sodium lignin sulfonate prepared above and reduce the stabilized ruthenium-cobalt bimetallic catalyst Ru-Co@SLS in water phase. aq -2 and 1 mmol of diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen for 4-5 times, and then 1.5 MPa of H2 was filled in, and the reaction was carried out at 80 °C for 4 h under stirring at 400 rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 5.
[0096] Take 6 mL of the sodium lignin sulfonate prepared above and reduce the stabilized ruthenium-cobalt bimetallic catalyst Ru-Co@SLS in water phase. aq -2 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPaH2 was filled in, and the reaction was carried out at 90℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 6.
[0097] Table 5 Comparative performance of catalysts for diphenylmethane hydrogenation
[0098]
[0099] Table 6 Comparative performance of catalysts for catalytic hydrodeoxygenation of o-hydroxydiphenylmethane
[0100]
[0101] [Comparative Example 3] Ru-Co@SLS aq -3 preparation and its catalytic performance
[0102] 60 mg of sodium lignin sulfonate was added to 2 mL of ultrapure water and stirred at room temperature until fully dissolved. 0.04 mmol of ruthenium acetate and 0.06 mmol of cobalt acetate were added to 2 mL of ultrapure water and ultrasonicated until completely dissolved. They were added dropwise to the aqueous solution of sodium lignin sulfonate. 2 mL of ultrapure water was added to the obtained mixture, and the mixture was reacted at 60 ° C for 3 h under magnetic stirring at 400 rpm, cooled to room temperature, and diluted ten times with ultrapure water to obtain Ru-Co@SLS. aq -3.
[0103] Take 6 mL of the sodium lignin sulfonate prepared above and reduce the stabilized ruthenium-cobalt bimetallic catalyst Ru-Co@SLS in water phase.aq -3 and 1 mmol of diphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5 MPa of H2 was filled in, and the reaction was carried out at 80 °C for 4 h under stirring at 400 rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 5.
[0104] Take 6 mL of the sodium lignin sulfonate prepared above and reduce the stabilized ruthenium-cobalt bimetallic catalyst Ru-Co@SLS in water phase. aq -3 and 1mmol o-hydroxydiphenylmethane were added to a stainless steel autoclave, the air was replaced with hydrogen 4-5 times, and then 1.5MPaH2 was filled in, and the reaction was carried out at 90℃ for 4h under stirring at 400rpm. After the reaction, the gas chromatography analysis results of the supernatant of the reaction system are shown in Table 6.
Claims
1. A water-phase reduction-stable ruthenium-cobalt bimetallic catalyst, characterized in that Ruthenium acetate and cobalt acetate are used as metal precursors at the same time, and demethylated modified sodium lignin sulfonate is used as a reducing agent and a stabilizer in an aqueous solution. No other chemical reagents and organic solvents are added to directly prepare a stable aqueous phase ruthenium cobalt bimetallic catalyst. The preparation process is as follows: Dissolve the vacuum-dried sodium lignin sulfonate in a 1-10% sodium hydroxide aqueous solution at a ratio of 3 mL per gram of sodium lignin sulfonate, and add anhydrous sodium sulfite at a ratio of 0.02-0.3 g per gram of sodium lignin sulfonate, stir until fully dissolved, react the mixture at 60-100°C for 1.5 hours, put it into a dialysis bag and dialyze it to neutrality, and then dry it to obtain demethylated modified sodium lignin sulfonate; According to the demethylation modification sodium lignin sulfonate per gram 1.67×10 -3 Weigh ruthenium acetate and cobalt acetate in the ratio of mol of the total amount of metal salt, wherein the molar fraction of ruthenium acetate is 40-60% of the total amount of metal salt, dissolve in ultrapure water and add dropwise into the demethylated modified sodium lignin sulfonate aqueous solution, add ultrapure water to the concentration of demethylated modified sodium lignin sulfonate to be 10 g / L, stir and react at 60°C for 3 h, cool to room temperature and dilute ten times with ultrapure water to obtain a ruthenium cobalt bimetallic catalyst stable to aqueous phase reduction.
2. Use of the aqueous phase reduction-stable ruthenium-cobalt bimetallic catalyst according to claim 1 in catalyzing the hydrogenation of diphenylmethane or the hydrodeoxygenation of o-hydroxydiphenylmethane.